PENDIDIKAN LINGKUNGAN HIDUP TENTANG BAHAYA POLUTAN UDARA - Indyah Sulistyo Arty (Jurnal Cakrawala Pendidikan, 2005)
AbstractApproached science technology society and environment has been used in curricullum 2004, with emphesized on student competency, while environmental education is not included in this curriculum. EnvironmentalEducation concerning with environmental issue is suitable integrated in science subject especially biology, chemistry, physics, and geography and help student understand their environmental problem to solve.One of the important environmental issue is about the danger of toxic air polutant. Teacher should be supported with new enriched subject material about dangerous air pollutant in order to integrate and implement it.Key words: environmental education, toxic air pollutant